Infection control and outcome of staged reverse shoulder arthroplasty for the management of shoulder infections - Boelch, Sebastian Philipp (JSES Int, 2020)
BACKGROUND: The treatment of septic arthritis, caused by either hematogenous seeding, injections, or surgery, can be challenging. Staged reverse shoulder arthroplasty (RSA) with temporary implantation of an antibiotic-loaded spacer is widely accepted but still discussed controversially. This study investigated the shoulder-specific bacterial spectrum, infection control rate, functional outcome, and infection-free survival rate after staged RSA in the mid- to long-term follow-up. It was hypothesized that staged RSA would show a high infection-free survival rate. METHODS: A total of 39 patients treated with staged RSA for primary septic arthritis (n = 8), secondary infection (n = 8), or periprosthetic infection (n = 23) were retrospectively included. The infection control rate was calculated based on cultures taken intraoperatively at spacer removal and RSA implantation. Infection-free survival was defined as no revision due to infection. The minimum follow-up period for functional outcome assessment was 2 years (n = 14; mean, 76 months; range, 31-128 months). RESULTS: Cutibacterium (26%) and coagulase-negative staphylococci (23%) were the predominant pathogens. The infection control rate was 90%. The cumulative infection-free survival rate was 91% after 128 months. Follow-up examinations showed a mean Constant score of 48 (range, 7-85), a mean QuickDASH (short version of Disabilities of the Arm, Shoulder and Hand questionnaire) score of 40.0 (range, 11.4-93.3), and a mean pain score of 1.6 (range, 0-7). CONCLUSION: Staged RSA implantation was confirmed to be a reliable treatment option for primary, secondary, and periprosthetic infections of the shoulder. The infection control rate and infection-free survival rate are satisfactory. However, patients and surgeons must be aware of functional impairment even after successful treatment of infections.